Yes, he can: Trump provokes a trade war. A clever EU will refrain from further tariffs but hold firm on WTO rules - Bettina Rudloff (Stiftung Wissenschaft und Politik (SWP), 2018)
The transatlantic trade dispute is escalating: After the United States (US) introduced additional tariffs on steel and aluminium, hectic negotiations began with the European Union (EU). First, the EU obtained a temporary derogation before increasing tariffs on a long list of particularly symbolic and politically sensitive products, such as orange juice and Harley-Davidson motorcycles. At the same time, the EU, in concert with other states, made the first move in a possible World Trade Organization (WTO) dispute procedure against the US. The US, in the meantime, has signalled the next round by deciding to examine options for tariffs on cars. Existing multinational rules leave only a limited scope for tariff increases, all of which bear the risk of further escalation. It would therefore be wise for the EU not to exhaust this leeway but to keep cool and stay liberal in its approach to trade.
Keywords: 320